2004
DOI: 10.1097/01.sla.0000109146.72827.76
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for the Treatment of Moderately or Well-Differentiated Hepatocellular Carcinoma

Abstract: The routine pre-orthotopic liver transplantation tumor grading may represent a valid tool in the selection of unresectable HCC patients for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
251
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(268 citation statements)
references
References 46 publications
12
251
2
3
Order By: Relevance
“…Several transplant groups have demonstrated that, apart from number and size of tumor nodules, parameters of tumor biology, such as differentiation and microvascular tumor invasion (MVI) play an important role for predicting patient prognosis, and should be, therefore, incorporated in the pretransplant selection process (4,8,9,10,11). However, since expanding the selection criteria may increase the risk of tumor relapse, its justification will very much depend on outcome of posttransplant HCC recurrence (13)(14)(15)(16)(17)(18)(19) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transplant groups have demonstrated that, apart from number and size of tumor nodules, parameters of tumor biology, such as differentiation and microvascular tumor invasion (MVI) play an important role for predicting patient prognosis, and should be, therefore, incorporated in the pretransplant selection process (4,8,9,10,11). However, since expanding the selection criteria may increase the risk of tumor relapse, its justification will very much depend on outcome of posttransplant HCC recurrence (13)(14)(15)(16)(17)(18)(19) …”
Section: Introductionmentioning
confidence: 99%
“…As of recent, there is increasing concern that organ allocation based on these stringent selection variables might exclude a significant number of patients who, although not meeting the Milan criteria, would nonetheless benefit from LT (8)(9)(10)(11)(12). Several transplant groups have demonstrated that, apart from number and size of tumor nodules, parameters of tumor biology, such as differentiation and microvascular tumor invasion (MVI) play an important role for predicting patient prognosis, and should be, therefore, incorporated in the pretransplant selection process (4,8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the criteria proposed by the University of Pittsburgh and some groups in Europe are based, at least in part, on pathological features (nodal invasion, grade, vascular invasion) that are not usually available before transplantation (9,21,50,68) . By contrast, the MC, UCSF and Onaca et al (42) proposal rely on factors (tu- ITT = intention to treat ¥ = patient survival (PS) ² = recurrence free rate (RR) Staging refers to the method used for tumor staging.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that some tumor patients transplanted outside of the UNOS and MC survive longer (9,12,16,17,18,36,44,52) and as consequence, several proposals have been made to expand the HCC inclusion criteria (18,28,63,64,65) . However, the criteria proposed by the University of Pittsburgh and some groups in Europe are based, at least in part, on pathological features (nodal invasion, grade, vascular invasion) that are not usually available before transplantation (9,21,50,68) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation